Household Food Insecurity and Maternal and Child Nutritional Status: Evidence from Maharashtra. (26th July 2019) - Maitra, Chandana; Sethi, Vani; Unisa, Sayeed; Shankar, Sriram
Abstract : In this paper we rigorously examine the association of household food security status with maternal and child nutritional status exploring a rich micro‐level database, the Comprehensive Nutrition Survey Maharashtra 2012. Using Household Food Insecurity Access Scale (HFIAS) as a metric to measure household food security, we apply simultaneous probit models to estimate the effect of food insecurity on maternal and child nutritional outcomes. The modelling framework addresses possible endogeneity in the above relationship. Findings indicate that household food insecurity increases the risk of maternal and child underweight with no effect on child stunting, wasting or maternal overweight. Women's decision‐making power mediates these associations. Food security interventions should be effective in tackling the concerns with undernutrition, however, food alone is not the solution. A mix of nutrition‐specific and nutrition‐sensitive policies is warranted. Food security interventions should be integrated into policies for human development.